″A Problems of using the technology of concentrated learning in higher education″ - Bakatanova, V. B.; Ignatov, S. V. (Problems of Engineer-Pedagogical Education, 2018)
The search for effective teaching technologies in higher education is conditioned by significant changes in the educational system of Ukraine. Based on the analysis of studies on the use of intensive training, the prospects for concentrated learning in higher education were determined. This is a system of organization of the educational process, in which the concentration of working time of students and teachers is ensured. A deeper study of disciplines is achieved by combining classes into blocks and reducing the number of subjects that are studied in parallel over time. The goal, essential features, advantages and disadvantages of concentrated learning were identified. Based on the analysis of the opinions of teachers and students of Ukrainian Engineering and Pedagogical Academy regarding the experimental introduction of this technology into the educational process, the pedagogical conditions for the effective application of the technology of concentrated learning in higher education were determined. Educational potential of the technology under focus is limited by its time-consuming nature and the need for systematic training which will create necessary conditions aimed to help future specialists acquire professional competencies.